The effects of three months long continuous glucose monitoring in children with type 1 diabetes on multiple daily insulin injections - Bukara-Radujković, Gordana; Miljković, Vesna; Lakić, Siniša (Vojnosanitetski pregled, 2021)
Background/Aim. The Professional System of Continuous Glucose Monitoring, the iPro®2 CGM System (Medtronic) is designed to be worn together with a glucose sensor with an electrode inserted into the subcutaneous tissue, up to 7 days, without insight into the current level of glycemia. After reading data from the iPro®2 device, a realistic picture of the glycemia movement during the period of wearing the device is obtained. The aim of the study was to examine whether objective measurement information collected through the use of professional continuous glucose monitoring (CGM) contribute to improved metabolic control in children with type 1 diabetes mellitus who are on the multiple daily insulin injections (MDI). Methods. The study was conducted on 24 patients (14 girls) aged 5 to 18 years, with an average age 12 ± 3.3 years, in the period from June to December 2016 in the Clinic of Pediatrics, University Clinical Center of the Republic of Srpska in Banja Luka. Glycated hemoglobin (HbA1c) was measured in the laboratory at the start of the trial and 3 months afterwards in order to determine the effect of wearing professional iPro®2 on metabolic control, and then three months later, to test for the long-lasting effects in the absence of iPro®2 monitoring. Results. The initial HbA1c was 7.78 ± 1.17% (min: 5.50%; max: 10.00%). After 3 months, HbA1c showed a statistically significant decrease to 7.34 ± 0.84% (min: 5.60%, max: 8.90%). At the six-month follow-up visit, without implementing professional CGM in the meantime, a significant increase in HbA1c was reached, with the average value of 7.68% ± 0.83% (min: 5.50%, max: 9.10%). Conclusion. This study shows that carrying a professional CGM for 7 days per month, 3 months continuously is associated with certain improvement of metabolic control in children with diabetes who are on MDI without increasing risks of hypoglicemia.
Keywords: diabetes mellitus, type 1; child; bosnia and herzegovina; drug monitoring; insulin; blood glucose self monitoring.